Study on Epidemiology of Chronic Obstructive Pulmonary Disease (COPD) at Western Regional Hospital, Pokhara - Ghosh, Vivek; Lamichhane, S; Thakuri, SB; Khadka, KCS; Teli, SS; Adhikari, SS; Shrestha, S; Acharya, SK; Subedi, SS (Journal of Gandaki Medical College-Nepal, 2017)
According to the curriculum of Bachelor of Medicine and Bachelor of Surgery (MBBS) program of the Tribhuvan University (TU), Institute of Medicine (IOM), the Department of Community Medicine of Gandaki Medical College (GMC) has been conducting the District Health System Management (DHSM) study for the students of MBBS, third phase (4th year). This program provides us an opportunity for clinical and community orientation to develop skills to become a competent medical professional to work at different levels of hospitals and district health system. This course enables us to assess resource potentials and constraints, prioritize the health problems and set strategies for solving them. It also enables us to be able to work in promotive, preventive, curative and rehabilitative health services as part of district health team. The program begins with theory classes on management and orientation classes at the college and placement of the students in three different places with rotation along with field supervisions in between. Here we are presenting our investigations on epidemiology of chronic obstructive pulmonary disease made at Western Regional Hospital during our District Health System Management (DHSM) study in third phase (Fourth year).Journal of Gandaki Medical College Volume, 09, Number 2, July December  2016, Page: 65-69